A Theory of Indigenous Entrepreneurship in the Modern African State: The Case of South Africa and Zimbabwe. Issue 2 (3rd July 2021) - Tshikovhi, Ndivhuho
Abstract: It is argued in this article that many modern-day African states share a set of characteristics in their political ideology and economic doctrines which stem from a shared history of colonialism and forms of foreign occupation and subjugation of indigenous peoples. Policies such as black economic empowerment (BEE) in South Africa and indigenisation and economic empowerment (IEE) in Zimbabwe are archetypes of this policy explicitly aligned with this indigenisation project and designed to promote indigenous people's participation in economic activities. In the context of this political economy of empowerment-oriented political ideology and legislative and policy frameworks in African states, this article seeks to define the features of indigenous entrepreneurship, which is the natural focus of much of the indigenisation project. It is theorised in this article that these factors combine to form a unique type of entrepreneurship, here termed indigenous entrepreneurship in the modern African state.